Prognostic value of neutrophil to lymphocyte ratio in acute ischemic stroke after reperfusion therapy - Ying Bi (Nature Portfolio, 2021)
Abstract The purpose of this study was to investigate whether baseline neutrophil to lymphocyte ratio (NLR) was an independent predictor for early symptomatic intracranial hemorrhage (sICH), poor functional outcome and mortality at 3 months after reperfusion therapy in acute ischemic stroke (AIS) patients. Using PubMed and EMBASE, we searched for literature published before January 19th, 2019. Two reviewers independently confirmed each study’s eligibility, assessed risk of bias, and extracted data. One reviewer combined studies using random effects meta-analysis. 9 studies with 3651 patients were pooled in the meta-analysis. Overall, baseline NLR levels were greater in patients with poor outcome. The standardized mean difference (SMD) in the NLR levels between patients with poor functional outcome (mRS > 2) and good functional outcome (mRS ≤ 2) was 0.54 units (95% credible interval [CI] [0.38, 0.70]). Heterogeneity test showed that there were significant differences between individual studies (p = 0.02; I2 = 72.8%). The NLR levels were associated with sICH in four included studies (n = 2003, SMD = 0.78, 95% [CI] [0.18, 1.38], I2 = 73.9%). Higher NLR levels were positively correlated with 3-month mortality (n = 1389, ES = 1.71, 95% CI [1.01,2.42], p < 0.01, I2 = 0%) when data were used as categorical variables. Our meta-analysis suggests that increased NLR levels are positively associated with greater risk of sICH, 3-month poor functional outcome and 3-month mortality in AIS patients undergoing reperfusion treatments. Although there are some deficits in this study, it may be feasible to predict the prognosis of reperfusion therapy in AIS patients with NLR levels.